Numerische Berechnung des Verschleißes an der Dornwalze eines Ringwalzprozesses in Abhängigkeit prozessrelevanter Parameter. Issue 7 (24th July 2014) - Behrens, B.‐A.; Lütke‐Verspohl, I.; Bouguecha, A.; Matthias, T.
<x xml:space="preserve">Abstract</x> Ring rolling is a forming process for the production of seamless rings. The process is characterized by a complex interaction of the shaping rollers and the centering rollers. In the design of a ring rolling process, it is necessary that the rolling and pre‐ring geometry strategy, i.e. the speeds and feeds of the individual rollers to align such that the required final shape is achieved optimally. Using the finite element simulation before starting the production optimizations concerning the process can be performed and thereby the number of costly rolling samples be kept to a minimum. The objective of the work focuses on the finite element modeling of a ring rolling process and the numerical calculation of the wear at the mandrel caused of the variation of process‐related parameters.